Effects of individual, family and community factors on the willingness of institutional elder care: a cross-sectional survey of the elderly in China - Wang, Zhaoqing (BMJ Open, 2020)
OBJECTIVE: To investigate the effects of the willingness to live in elder care institutions associated with individual factors, family environment and the community environment in the elderly in China. DESIGN: Cross-sectional survey. SETTING: Heilongjiang Province, China. PARTICIPANTS: A total of 1003 elderly people were selected through multistage sampling in Heilongjiang Province. PRIMARY AND SECONDARY OUTCOME MEASURES: A multistage, stratified sampling design was employed. Differences in health status, family environment and community environment of the respondents were compared with the t-test and χ(2) test. Logistic regression analysis was performed to assess key determinants of willingness to live in institutions. RESULTS: This study showed that 45.4% of respondents were willing to live in elder care institutions in the future. Factors influencing willingness to live in elder care institutions were age, house ownership, living with spouse and children, disease caregivers and availability of home healthcare services. The elders who had no property (OR=2.37, 95% CI 1.750 to 3.200, p<0.01) and those aged 80 or above (OR=2.25, 95% CI 1.490 to 3.400, p<0.01) were, respectively, 2.370 and 2.250 times more receptive to living in elder care institutions than their control groups. However, those living with a spouse (OR=0.47, 95% CI 0.287 to 0.762, p<0.01), living with children (OR=0.25, 95% CI 0.158 to 0.402, p<0.01) or living with a spouse and children (OR=0.29, 95% CI 0.160 to 0.509, p<0.01) were less willing to live in elder care institutions. CONCLUSIONS: These results suggest that the willingness to enter elder care institutions is affected by individual, family environmental and community environmental factors. We should vigorously develop community-centred intensive home-based elder care services by improving the quality and availability of home health services by expanding investment in the community.